PENGARUH DIFERENSIASI PRODUK TERHADAP MINAT KONSUMEN DALAM RANGKA MEMENANGKAN PERSAINGAN BISNIS JASA ASURANSI PADA PT. PRUDENTIAL LIFE ASSURANCE PEKANBARU - Pratama, Yoga; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In product differentiation, the product has meaning or value that the company creates a new product is perceived by customers as a whole is unique and different products. In this case, the product in question is the quality of the product that will support the product position in the market. Quality can be defined as a comparison with alternative competitor from the market's view. Consumer interest is growing because of a consumer desire and have interest in the product is needed. Based on the motives of consumers in accordance with the wishes and meet their needs, the company must create a product that is different and has advantages over competitors in the business services including insurance. a ministry of service, based on these two companies should be appropriately design a marketing strategy to attract the interest of the consumers themselves in order to gravitate toward product and services offered so that if consumers have an interest in those products then there will be a decision to buy the product.This research was conducted at PT. Prudential Life Assurance Pekanbaru is located on the road Tuanku Tambusai Paninsula complex BI B / 8, Pekanbaru. The purpose of this research was conducted to determine the effect of product differentiation against consumer interest in PT. Prudential Life Assurance Pekanbaru.In this research methodology is descriptive and quantitative with SPSS, where samples were used that policyholders / consumers PT.Prudential Life Assurance Pekanbaru and as a source of information is the GA Office and Personal Assistant. To determine the sample using the formula Slovin, sampling with accidental sampling method. Techniques of collecting data through interviews, observation and questionnaires.From the results of data analysis includes test validity, reliability, and simple linear regression, product differentiation in this study included five components of either the form, features, quality of performance, quality, relevance, and reliability, process. Each one has an indicator interrelated and positive influence on consumer interest in PT. Prudential Life Assurance Pekanbaru.Keyword: Differentiation Products, Consumer Interests